The Role of Scout Extracurricular Activities on the Formation of Student Leadership Character at Boarding School - Nabila Farhana; Rizki; Badrus; Tiara, Cut (Journal of Social and Scientific Education, 2024)
This research aims to determine the role of extracurricular scouting in the formation of student leadership character at the Darul Muttaqien Islamic Boarding School. The research approach used is qualitative, with a focus on an in-depth understanding of the experiences and perceptions of students involved in scouting activities at Islamic boarding schools. This research method uses questionnaires, participant observation, and document analysis as data collection tools. Data was collected using a questionnaire from 56 Darul Muttaqien Islamic Boarding School student respondents using a purposive sampling technique, then the data was analyzed using David Kolb's Learning Inventory theory. The results of this research show that scouting extracurriculars plays a very important role in shaping students' leadership character. Students who are actively involved in scouting tend to be able to develop courageous leadership skills, responsibility, and cooperation. These findings provide valuable insight for other schools to develop student leadership character in more effective scouting extracurricular programs.